Model Pembagian Hasil dalam Aqad Mukhabarah: Studi Kasus Dua Pemilik Lahan di Desa Sitopayan - Natassia, Putri; Efendi, Rahmad (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
Indonesia is a large agricultural country, and most of its territory consists of fertile land and abundant water. This has resulted in the majority of Indonesian people living as farmers. The shortage of agricultural land results in farmers who do not have land working on other people's land and collaborating in the agricultural sector between land owners and cultivators. In the compilation of sharia economic law, cooperation in the field of agriculture (rice fields) is divided into two, namely muzara'ah and mukhabarah. Farmers in Sitopayan Village, Portibi District have implemented this mukhabarah collaboration. However, farmers know him as Pabaenko Saba. This type of research is field research. Meanwhile, the nature of the research is descriptive. The data sources used are primary and secondary data sources. Data collection was carried out using interview techniques. The resulting data is described descriptively and analyzed using inductive thinking. The results of this research indicate that the implementation of profit sharing carried out by land owners and cultivators in Sitopayan Village, Portibi District is not in accordance with the provisions in the Compilation of Sharia Economic Law Article 260. The implementation of profit sharing is not in accordance with the Compilation of Sharia Economic Law, namely in terms of profit sharing What is done by the cultivator is not transparent to the land owner regarding the actual harvest.